SUITABLE SUBSTRATE VOLUMES AND CULTIVARS FOR ENHANCING GROWTH AND IN-CREASING YIELD OF YARD-LONG BEAN IN URBAN ECOSYSTEMS - Rizar, Fitra Fadhilah; Lakitan, Benyamin; Wijaya, Andi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Yard-long bean, a favored vegetable known for its taste and nutritional value, holds economic importance. Its climbing nature and environmental resilience make it ideal for urban cultivation in pots and climbing frames. This study, conducted in a limited urban space, aimed to determine optimal pot size and cultivars for yard-long bean cultivation, emphasizing growth and yield. Two pot sizes were used: a larger one (30 cm diameter x 37 cm height, M1) and a smaller one (30 cm diameter x 30 cm height, M2), alongside three commercial cultivars: Kanton Tavi (V1), Camellia (V2), and Arafi (V3). Results indicated that a larger pot size increased pod number and total pod weight per plant, facilitating root development, vine growth, and enhanced yield. The larger substrate volume retained moisture and boosted plant biomass. Cultivar treatment affected branch length and flowering time, with Camellia exhibiting the longest harvest period (14 harvests). Hence, for Camellia varieties, cultivation using larger pots (30 cm diameter x 37 cm height) is recommended.